2014
DOI: 10.1098/rsbl.2014.0588
|View full text |Cite
|
Sign up to set email alerts
|

Contrast influences female attraction to performance-based sexual signals in a songbird

Abstract: Animals do not make decisions in a bubble but often refer to previous experience when discriminating between options. Contrast effects occur when the value of a stimulus affects the response to another value of the stimulus, and the changes in value and response are in the same direction. Although contrast effects appear irrational, they could benefit decision makers when there is spatial or temporal variation and autocorrelation in the value of stimuli that elicit decisions. Here, we examined whether contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Several studies have found that extended exposure to songs of differing value influence neural activity and behavior in female and male songbirds. One week of experience with more attractive compared to less attractive songs increased neural discrimination for male song in the female European starling (Sturnus vulgaris) [Sockman et al, 2002;Sockman et al, 2005] and decreased behavioral responsiveness to male song in the female Lincoln's sparrow [Lyons et al, 2014], suggesting that long-term experience with attractive songs increases female discrimination of song attractiveness [Bateson and Healy, 2005;Sockman, 2007;Lyons et al, 2014]. At the same time, male songbirds that experienced 1 week of exposure to high-quality songs increased singing effort more than males that experienced low-quality songs, indicating that males increase competitive behavior in response to experience with competitive signals [Salvante et al, 2009;Sewall et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have found that extended exposure to songs of differing value influence neural activity and behavior in female and male songbirds. One week of experience with more attractive compared to less attractive songs increased neural discrimination for male song in the female European starling (Sturnus vulgaris) [Sockman et al, 2002;Sockman et al, 2005] and decreased behavioral responsiveness to male song in the female Lincoln's sparrow [Lyons et al, 2014], suggesting that long-term experience with attractive songs increases female discrimination of song attractiveness [Bateson and Healy, 2005;Sockman, 2007;Lyons et al, 2014]. At the same time, male songbirds that experienced 1 week of exposure to high-quality songs increased singing effort more than males that experienced low-quality songs, indicating that males increase competitive behavior in response to experience with competitive signals [Salvante et al, 2009;Sewall et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…In songbirds, the function of songs in the external environment and the state of the internal environment differ between females and males that are reproductively ready [Searcy and Brenowitz, 1988;Nowicki and Searcy, 2004]. For females, high-performance songs are attractive [Caro et al, 2010;Lyons et al, 2014], whereas for males, high-performance songs are threatening [Illes et al, 2006]. The finding of an interactive effect of song performance and sex on monoaminergic activity in the auditory telencephalon gives rise to the hypothesis that the evolution of sex differences in behavioral responses to sexual signals is mediated, at least in part, by monoamines in perceptual regions of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations